Characterization, Expression Profiling, and Functional Analysis of PtDef, a Defensin-Encoding Gene From Populus trichocarpa - Wei, Hui; Movahedi, Ali; Xu, Chen; Sun, Weibo; Wang, Pu; Li, Dawei; Yin, Tongming; Zhuge, Qiang (Frontiers in Microbiology, 2020)
PtDef contained eight cysteine domains specific to defensins. The qRT-PCR analysis showed that PtDef was expressed in all tissues tested, with lower expression in leaves and higher expression in petioles, stems, and roots. Purified fused PtDef inhibited Aspergillus niger, Alternaria Nees, Mucor corymbifer, Marssonina populi, Rhizopus sp., and Neurospora crassa. In addition, the PtDef inhibits the growth of Escherichia coli by triggering autolysis. PtDef overexpression in Nanlin895 poplar (Populus × euramericana cv. Nanlin895) enhanced the level of resistance to Septotinia populiperda. Moreover, qRT-PCR showed that the expression of 13 genes related to salicylic acid (SA) and jasmonic acid (JA) signal transduction differed between transgenic and wild-type (WT) poplars at 0, 12, 24, 48, and 72 h after inoculation, and the expression of PR1-1 (12–72 h), NPR1-2, TGA1, and MYC2-1 was higher in transgenic than in WT poplar. Furthermore, during the hypersensitivity response, a large amount of H2O2 was produced by the poplar lines, particularly 12–24 h after inoculation, and the rate and magnitude of the increase in H2O2 concentration were greater in transgenic than that in WT poplar. Overall, our data suggest that PtDef, a defensin-encoding gene of P. trichocarpa, could be used for genetic engineering of woody plants with enhanced resistance to disease.